MEMPERTAHANKAN IDENTITAS LOKAL DI ERA GLOBALISASI MELALUI SANGGAR SENI BOUGENVILLE - Jagad aditya dewantara; Ega Nur Cahya; Sulistyarini; Efriani; Shilmy Purnama; Afandi (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2022)
This study aims to determine how the Bougenville studio maintains the local identity in the era of globalization.The research is qualitative with case study method. The the subjects of this study were the head of the Bougenville studio, the trainer of the Bougenville studio, the students of the Bougenville studio and the community. The data were collected through observation, interviews, and documentation. The data were analyzed using data reduction, data presentation, and drawing conclusions. The results showed that the Bougenville studio applies a strategy in keeping students safe and maintaining the local identity. The regular training programs and level ups are included in the studio curriculum. However, in this Bougenville studio, the local culture is instilled, or focuses more on the regional culture, namely Malay. However, it does not make the students of the Bougenville studio experience an ethnocentric attitude. Bougenville Studio is able to defend. All citizens uphold civic culture values such as solidarity, tolerance, active involvement and responsibility